Areca palm velarivirus 1 infection caused disassembly of chloroplast and reduction of photosynthesis in areca palm - Cao, Xianmei; Gao, Baosen; Lu, Jie; Wang, Hongxing; Zhao, Ruibai; Huang, Xi (Frontiers in Microbiology, 2024)
The expansion of betel palm cultivation is driven by rising demand for betel nut, yet this growth is accompanied by challenges such as decreased agricultural biodiversity and the spread of infectious pathogens. Among these, Yellow Leaf Disease (YLD) emerges as a prominent threat to betel palm plantation. Areca Palm Velarivirus 1 (APV1) has been identified as a primary causative agent of YLD, precipitating leaf yellowing, stunted growth, and diminished yield. However, the precise mechanisms underlying APV1-induced damage remain elusive. Our study elucidates that APV1 infiltrates chloroplasts, instigating severe damage and consequential reductions in chlorophyll a/b and carotene levels, alongside notable declines in photosynthetic efficiency. Moreover, APV1 infection exerts broad regulatory effects on gene expression, particularly suppressing key genes implicated in chloroplast function and photosynthesis. These disruptions correlate with growth retardation, yield diminishment, and compromised nut quality. Intriguingly, the paradoxical destruction of the host's photosynthetic machinery by APV1 prompts inquiry into its evolutionary rationale, given the virus's dependence on host resources for replication and proliferation. Our findings reveal that APV1-induced leaf yellowing acts as a beacon for transmission vectors, hinting at a nuanced "host-pathogen-vector co-evolutionary" dynamic.